2015
DOI: 10.3126/ijasbt.v3i3.13218
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Demodectic Mange in Canines of Kathmandu Valley having Skin Disorder and Its Associated Risk Factors

Abstract: Very little information is available regarding the demographics of the demodicosis in canines of Kathmandu valley and in Nepal as a whole. In this study, we determined the prevalence of the demodicosis and its associated risk factors from 110 canines of Kathmandu valley including both sheltered and free-roaming. The skin scrapping collected was dissolved in 10% KOH for the microscopic diagnosis of the mites. The overall prevalence of demodectic mange was found to be 29.1%. There was significant difference (p&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 12 publications
6
14
0
2
Order By: Relevance
“…The overall prevalence of demodicosis in the present study is comparable with the rates reported from Kathmandu Valley (Nepal) (29.1%) and Mexico (23%) (Rodriguez-Vivas et al, 2003;Shrestha et al, 2015). Male dogs were more frequently affected than females.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The overall prevalence of demodicosis in the present study is comparable with the rates reported from Kathmandu Valley (Nepal) (29.1%) and Mexico (23%) (Rodriguez-Vivas et al, 2003;Shrestha et al, 2015). Male dogs were more frequently affected than females.…”
Section: Discussionsupporting
confidence: 87%
“…Demodicosis is often diagnosed in puppies and young dogs (Scott & Paradis, 1990;Shipstone, 2000;Shrestha et al, 2015). There are two types of demodicosis, including the localized (often found in puppies) and generalized forms.…”
Section: Discussionmentioning
confidence: 99%
“…Among 171 total rescued dogs, 69 (40.35%) were suspected for mange infestation. Bindari et al (2012) studied the prevalence of mange infestation in street dogs in Kathmandu Valley, Nepal. They took samples from 60 suspected positive street dogs and confirmed 67% positive.…”
Section: Resultsmentioning
confidence: 99%
“…Very few published data are available regarding the health problems of street dog in Nepal. Bindari et al (2012) studied the prevalence of mange in street dogs in Kathmandu, Nepal. They took samples from 60 positive suspected street dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of Circulatory Concentration of Cytokines Platelet-Derived Growth Factor-BB, Transforming Growth Factor Beta-1, and IL-10 in Canine Generalized Demodicosis Mayank Parwari 1 *, GC Mandali 2 , Jignasha M Parmar 3 , RA Mathakiya 4 IntroductIon D emodicosis, also named as demodectic mange, red mange, or follicular mange, can be defined as a common but exigent, inflammatory, noncontagious parasitic dermatosis caused by over the population of the host-specific follicular mites of various Demodex species (Ravera et al, 2015;Shrestha et al, 2015). Canine generalized demodicosis (CGD) may be a severe and potentially life-threatening disease.…”
mentioning
confidence: 99%